DISSERTATION TITLE: SURVIVABILITY TECHNIQUES FORRESTORING CONNECTED COVERAGE IN WIRELESS SENSOR AND MOBILE ACTOR NETWORKS - HAIDER, NOMAN (2014)
Wireless sensor and mobile actor networks (WSMANs) are captivating growing attention because they not only boost existing sensor network applications but also introduce wide range of novel applications that require autonomous, active, and intelligent interaction with the environment. Examples of such applications include military (e.g., homeland security, battlefield reconnaissance, landmine detection and deactivation), critical infrastructure protection (e.g., oil & gas pipeline monitoring and maintenance) and civilian (e.g., disaster management). . In these applications, maintaining actor connected coverage is extremely crucial for successful operation of WSMAN because mobile nodes have to collaborate on the data received from sensors and perform optimal coordinated response against the reported events. However, failure of an actor may partition the network into disjoint segments besides leaving unattended sensors (i.e., coverage) and thus disrupts the operation.